New neurons in the adult striatum: from rodents to humans - Inta, Dragos; Cameron, Heather A.; Gass, Peter (Trends in neurosciences, 2015)
Most neurons are generated during development and are not replaced during adulthood, even if they are lost to injury or disease. However, it is firmly established that new neurons are generated in the dentate gyrus of the hippocampus of almost all adult mammals, including humans. Nevertheless, many questions remain regarding adult neurogenesis in other brain regions and particularly in humans, where standard birth-dating methods are not generally feasible. Exciting recent evidence indicates that calretinin-expressing interneurons are added to the adult human striatum at a substantial rate. The role of new neurons is unknown, but studies in rodents will be able to further elucidate their identity and origin and then we may begin to understand their regulation and function.
Gesehen am 26.11.2018
Available online 20 August 2015